Periaqueductal Grey differential modulation of Nucleus Accumbens and Basolateral Amygdala plasticity under controllable and uncontrollable stress - Omer Horovitz (Nature Portfolio, 2017)
Abstract Resilience has been conceptualized in part as a dynamic process that includes the ability to adapt to stressful conditions. As such it encompasses the extent to which neural plasticity may be promoted. The current study examined metaplasticity by referring to the “plasticity of synaptic plasticity” in a neural circuit composed of the basolateral amygdala (BLA) and the nucleus accumbens (NAcc), using behavioural stress controllability with or without preceding stimulation of the dorsal periaqueductal gray (i.e. dPAG priming). A tendency for increased plasticity in the controllable versus the uncontrollable group was found in both the BLA and NAcc. dPAG priming suppressed NAcc LTP in all groups, but it suppressed BLA LTP only in the uncontrollable group, demonstrating dissociation between either controllable and uncontrollable groups or the NAcc and BLA. Thus, metaplasticity in the dPAG-BLA-NAcc circuit regulated differentially by controllable or uncontrollable stress may underlie stress coping, and thus contribute to stress-related psychopathologies.